A novel HLA‐B*54 allele, B*54:16. Issue 1 (6th December 2012) - Gong, Z.; Zhang, Z. X.; Shan, X.; Li, D.; Li, W.
<x xml:space="preserve">Abstract</x> The HLA‐B*54:16 allele differs from the B*54:01 by one nucleotide substitution in exon 3 at NT412.